Coronary Flow Velocity and Coronary Flow Velocity Reserve in Children with Ventricular Septal Defect - Tamura, Masamichi; Aoki, Mieko; Toyono, Manatomo; Harada, Kenji (The Tohoku Journal of Experimental Medicine, 2004)
To assess coronary flow characteristics in congenital heart defect with left ventricular (LV) volume overload, we examined 24 children (mean 12.1±7.1 months) with ventricular septal defect. The pulmonary to systemic flow ratio ranged from 1.1 to 3.0. Control group consisted of 10 age-matched children who had a history of Kawasaki disease with angiographically normal coronary artery in the acute phase. LV end-diastolic volume and LV mass were measured by left ventriculogram. With Doppler flow guide wire (0.014-inch), average peak flow velocity (APV) in left anterior descending coronary artery was recorded at rest and during hyperemia (0.16 mg/kg/min adenosine infusion intravenously). Coronary flow velocity reserve (CFVR) was calculated as the ratio of hyperemic/baseline APV. Seven patients were also studied 5-7 months after surgery. Compared with control subjects, CFVR was significantly reduced in patients with LVvolume overload (1.78±0.24 vs. 2.66±0.42, p<0.0001) because baseline APV was significantly greater (30±8 vs. 23±5 cm/sec, p=0.0027). Significant correlations were observed between CFVR and Qp/Qs, baseline APV, LV end-diastolic volume, or LVmass. Stepwise regression analysis showed that baseline APV and Qp/Qs were important determinants of CFVR (CFVR=2.64−0.202 [Qp/Qs]−0.015 [APV] r=0.83, p<0.0001). In 7 patients with LVvolume overload, CFVR improved significantly after surgery because of reduction of baseline APV. CFVR is limited in patients with LV volume overload because of the elevation of baseline resting APV. LAD flow pattern is dependent on LV volume overload level and its changes after surgery.